Analisis Pendapatan Usaha Kelompok Wanita Tani Kecamatan Cilacap Tengah - Aditiya Kartika Dewi; Istiqomah Istiqomah; Arif Andri Wibowo (Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2024)
The development of the agricultural sector in enhancing national economic development aims to increase food production to meet domestic consumption. In the agricultural sector there are institutions that manage it, one of which is the Women Farmers Group (KWT). To manage the agricultural sector there are factors that affect KWT business income. The purpose of this study is to analyze the effect of capital, land area, number of workers and business diversification on KWT income. The Population in this study were 34 Women Farmer Groups (KWT) in Central Cilacap District, Cilacap Regency. The sample used was 34 KWT with saturated sampling method or census. Data collection techniques through interview methods based on questionnaires. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that the average income earned is 26.47% or Rp 188,000.00 - Rp 670.000,00 per one planting period. The capital variable has a significant effect on KWT operating income. The implication of this research is that KWT expands the land to increase the types of vegetable crops and their quality, increases the effectiveness of the performance of the number of workers and increases the types of business diversification by processing agricultural products so that they have a high selling value which can increase the income earned.